2008
DOI: 10.1371/journal.pone.0003549
|View full text |Cite
|
Sign up to set email alerts
|

Gene Disruption of Plasmodium falciparum p52 Results in Attenuation of Malaria Liver Stage Development in Cultured Primary Human Hepatocytes

Abstract: Difficulties with inducing sterile and long lasting protective immunity against malaria with subunit vaccines has renewed interest in vaccinations with attenuated Plasmodium parasites. Immunizations with sporozoites that are attenuated by radiation (RAS) can induce strong protective immunity both in humans and rodent models of malaria. Recently, in rodent parasites it has been shown that through the deletion of a single gene, sporozoites can also become attenuated in liver stage development and, importantly, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 64 publications
5
88
0
1
Order By: Relevance
“…However, the knockouts showed clear defects in liver-stage development. Recently, in an independent study, disruption of the P52 gene in P. falciparum has been achieved by single-cross-over integration (32). The observed phenotype was in agreement with the p52 Ϫ phenotype presented here.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the knockouts showed clear defects in liver-stage development. Recently, in an independent study, disruption of the P52 gene in P. falciparum has been achieved by single-cross-over integration (32). The observed phenotype was in agreement with the p52 Ϫ phenotype presented here.…”
Section: Discussionsupporting
confidence: 88%
“…The observed phenotype was in agreement with the p52 Ϫ phenotype presented here. However, single-cross-over recombination insertions are prone to reversion by plasmid excision, and indeed, the study by van Schaijk et al (32) observed reverting parasites that had restored WT growth. Our strategy for gene deletions was to use double-cross-over recombination gene replacement, which makes it impossible for the parasite to genet- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gliding assays and inhibition of sporozoite invasion assays were performed as described previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…The functions of these two proteins appear to be different because the deletion of either gene influences the ability of the parasite to efficiently infect hepatocytes, with no effect on their ability to invade salivary gland cells in the mosquito (22,23). In P. berghei there is also evidence that these genes may be required for invasion of hepatocytes and to promote normal development in the liver.…”
mentioning
confidence: 99%